Book Review: Ecological Pedagogy, Buddhist Pedagogy, Hermeneutic Pedagogy: Experiments in a Curriculum for Miracles - Haggarty, Holly Tsun (Journal of the Canadian Association for Curriculum Studies, 2016)
Jackie Seidel and David Jardine’s book Ecological Pedagogy, Buddhist Pedagogy, Hermeneutic Pedagogy: Experiments in a Curriculum for Miracles both diagnoses and offers a remedy for the ills of modern, Western education. The book is, indeed, about miracles, but it starts with a re-interpretation of the meaning of miracle, suggesting that miracle is not something imposed on a problem to effect a wondrous transformation, but the transformative effect of wonder itself. Wonder is an attitude that the authors see as arising from a pedagogy based on ecological awareness, interpretive inquiry, and most of all, from the Buddhist precept of “dependent co-arising”—the idea that all beings exist, not autonomously, but in relation with each other. The book discusses both philosophical concepts of the three pedagogical disciplines as well as practices that arise from them.